Stretching the c-axis of the Mn3O4 lattice with broadened ion transfer channels for enhanced Na-ion storage. Issue 41 (13th October 2021) - Wang, Shiyu; Zhao, Rui; Yao, Shuyun; Li, Bingcan; Liu, Ruochen; Hu, Lingyuan; Zhang, Anqi; Yang, Ru; Liu, Xia; Fu, Zhenzhen; Wang, Dewei; Yang, ZhiYu; et al.
Abstract : C -Axis stretched lattice distorted Mn3 O4 is achieved by a simple sulfurization/desulfurization treatment. The resultant Ov-Mn3 O4 exhibits accelerated electronic and ionic transport kinetics, beneficial for the energy storage performance. Abstract : Mn3 O4 is a typical electrode material for supercapacitors with high theoretical energy density. However, the electrochemical performance of Mn3 O4 is hindered by the sluggish charge transfer kinetics and poor cycling lifetimes. Herein, Mn3 O4 with c -axis stretched lattice distortion (oxygen vacancy, Ov-Mn3 O4 ) was prepared through a simple sulfurization/desulfurization treatment. The resultant Ov-Mn3 O4 displays a high capacity of 331.1 F g −1 at 1 A g −1, a significant rate capability of 258.2 F g −1 at 20 A g −1, and a promising cycling stability with 83% capacity retention after 15 000 cycles. An asymmetric supercapacitor with Ov-Mn3 O4 as the cathode delivers an energy density of 52.5 W h kg −1 at a power density of 1000 W kg −1 . In situ Raman results demonstrate that Ov-Mn3 O4 can effectively suppress and accommodate the cooperative Jahn–Teller distortion, contributing to a prolonged cycling life. DFT results suggest that the c -axis stretched lattice distortion induces electron delocalization, thus facilitating the electron transfer. Moreover, Na + exhibits accelerated transfer kinetics in c -axis stretched lattice distorted Ov-Mn3 O4 with broadened ion transfer channels. This work highlights the advantage of c -axis stretched lattice distortion for Na ion storage in Mn3 O4, which can be expanded to optimize the electronic configuration of other metal oxides.